Demonstration of carcinoembryonic antigen (CEA) expression in normal, chronically inflamed, and malignant pancreatic tissue by immunohistochemistry. Issue 6 (June 1986) - Allum, W H; Stokes, H J; Macdonald, F; Fielding, J W
Abstract : The expression of carcinoembryonic antigen (CEA) was evaluated by immunoperoxidase staining with two anti-CEA monoclonal antibodies in normal, chronically inflamed, and malignant pancreatic tissue. Positive staining was not observed in normal specimens. In pancreatic cancer the expression of CEA was related to the degree of differentiation of the tumour. Positive staining was also observed in chronic pancreatitis.